The association of serum level of CTRP1 with Common Bile Duct Diameter and Other Manifestations in Patients with Non-alcoholic Fatty Liver - Ebrahimi, Reyhane; Zand, Shahabedin; Shanaki, Mehrnoosh (Archives of Medical Laboratory Sciences, 2019)
Background: Nonalcoholic fatty liver diseases (NAFLD) is one of the main chronic liver diseases and raises the risk of morbidity and mortality due to its inevitable outcomes. Understanding the clinical manifestations of the liver is critical to identify NAFLD patients with the greatest risk of developing nonalcoholic steatohepatitis and cirrhosis. In the liver, C1q/TNF-related protein 1 (CTRP1) modulates both glucose and lipid metabolism and improves insulin sensitivity which may affect the pathologies of the liver. Materials and Methods: This study was conducted on 22 patients with NAFLD confirmed by ultrasonography and 21 healthy subjects. Clinical and histological variables were analyzed. The ultrasonography procedure was used to quantity Common bile duct (CBD). Liver stiffness (LS) was measured by transient elastography. Results: There was a significant difference in CTRP1 levels between NAFLD patients and controls (p=0.032). Moreover, there was a significant positive correlation between CTRP1 level and liver enzymes including AST (r=0.667; p=0.001), ALT (r=0.433; p=0.044), and γ-GT (r=0.428; p=0.047) in NAFLD patients. There was also a significant positive correlation between CTRP1 level and CBD (r= 0.469; p=0.028) in NAFLD patients. Moreover, the largest CBD was measured as 5.99 mm. Conclusion: It seems that CTRP1 is a novel adipokine related to the pathogenesis of NAFLD and is associated with the clinical manifestations of the liver such as liver enzymes, and CBD.